Smart Vehicles for Smarter Cities: Context-Aware V2X to Improve QoI - Chagas, Amirton B.; Ferraz, Carlos A. G. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
Driving is changing due to more embedded intelligence in cars and to the networking capabilities now rising, making possible that vehicles, infrastructure units, drivers’, passengers’ and pedestrians’ smartphones and any other devices communicate with each other. A smart city can make use of the information available due to the connectivity of these devices to improve several aspects of its inhabitants daily life, traffic being one of the most important. Excess of information, however, can be harmful in a dangerous environment such as transit, where driver’s attention is key to the safety of everyone in cars and streets. Given this scenario, we propose researching the use of context-aware systems to identify the proper information to be provided to human drivers without distracting them from the driving activity, or to autonomous vehicles without saturating them with non-important information, thus reducing the processing power needed and improving the latency and quality of decisions made. In order to narrow the investigation, this work will be focused on the Quality of Information (QoI) to drivers and autonomous vehicles.